Preliminary analysis of patient assessment within a study on the impact of hydrokinetotherapy on body composition and metabolic disease risk in an adult population segment - Claudiu Cobuz; Sînziana Călina Silișteanu; Maricela Cobuz; Andrei-Ioan Costea; Elena Vizitiu Lakhdari (Balneo and PRM Research Journal)
In clinical and research settings, the accurate and reliable evaluation of body composition is necessary. Existing methods present various challenges, either in measurement methodology or in the assumptions they rely on.The purpose of this study is to conduct a preliminary analysis of patient assessment within a study concerning the impact of hydroki-netotherapy on body composition and metabolic disease risk in an adult population segment. Methods: The research was carried out at the Diabetes Ambulatory Clinic of the Suceava County Hospital in January 2024. An essential component of this investigation involves evaluating body composition parameters measured using the Tanita 738 device and assessing metabolic risk factors such as diabetes mellitus, hypertension, and dyslipidemia. In parallel with this research, a hydrokinetotherapy model adapted to this population is proposed for development. Results: The interpretation of BMI data for women aged 40-60 revealed significant variability in this group’s body composition, as was also observed in women aged 61-80. Among women aged 61-80, there was a significant proportion of participants with morbid obesity (BMI ≥ 40). Similarly, the BMI data for men aged 40-60 indicated notable variability in body composition, consistent with the findings for men aged 61-80. Both age groups in men exhibited significant overweight and obesity, highlighting the need for increased attention to weight management and metabolic health among men. Conclusions: The study on body composition and metabolic disease risk among adults aged 40 to 80, participants at the Diabetes Ambulatory Clinic of the Suceava County Hospital, demonstrated significant findings in both women and men. Implementing a 4-month hydrokinetotherapy program indicates an approach aimed at optimizing participants’ health. A personalized approach and careful management of hydrokineto-therapy exercises are necessary. Weight loss through diet and physical exercise is proven to be the most effective treatment strategy for obese and overweight elderly subjects, facilitating the maintenance of muscle mass and promoting functional recovery